Estudo das propriedades mecânicas, térmicas e de transporte do compósito com carbonato de cálcio nano e microparticulado em polipropileno - Barbosa, Juliano Martins (2011)
In this work were determined and compared to mechanical, thermal and barrier of the polypropylene composites containing micropartilate and microparticulate calcium carbonate. To prepare the composites, the filler was incorporated into the homopolymer PP, with the aid of the compatibilizer PP grafted with maleic anhydride in a twin-screw extruder, producing concentrates of calcium carbonate. Were subsequently diluted in PP, in different conditions and at four different concentrations. Based on the results of mechanical tests, the condition that generated the best result was obtained with screw speed of 500rpm and 10kg/h flow of the extruder. The other mechanical, thermal and barrier were performed on samples prepared in these processing conditions and from this point forward, we evaluated the influence of the concentration of filler on the test results, as well as the particle size. In this condition, the impact resistance of nanoparticulate increased from 4.60 to 4.96 KJ/m2 concentration of 7.87% of CaCO3. As for the Tensile strength, only 0.48% of nanoparticulate CaCO3 increased from 32.8 MPa to 35.2 MPa. HDT in the gain was 12ºC with respect to the homopolymer PP and a 2.9 ºC on the microparticulate composite. The addition of CaCO3 OOT reduced as its concentration increased and the flammability, the nanoparticulate compound showed a slight reduction in burning rate with respect to the PP. Regarding ownership of permeability to water vapor, the microparticle behave remained stable for all concentrations, however, as the oxygen permeability, we can highlight the compound with 1.51%. In the nanoparticles, we can highlight the compound with which generated a 0.48% reduction to 52% of the value found for the PP, but did not produce good results with oxygen. Comparing the results we can conclude that the composite nanoparticulate has interesting properties and superior to the microparticle, depending on its concentration.